2012
DOI: 10.1038/npp.2012.153
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-analysis of Factors Impacting Detection of Antidepressant Efficacy in Clinical Trials: The Importance of Academic Sites

Abstract: Variability in placebo response greatly complicates the design, conduct, and interpretation of clinical trials of antidepressant medications. To identify factors that impact detection of antidepressant-placebo differences, we conducted a meta-analysis of all relevant phase II-IV clinical trials for major depressive disorder conducted by the manufacturer of venlafaxine and desvenlafaxine completed by March 2011. We examined 15 factors potentially relevant to trial outcomes, using the standardized mean differenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
36
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 20 publications
(26 reference statements)
2
36
1
Order By: Relevance
“…In some of these meta-analyses, changing participant characteristics have been proposed to be responsible for the trend. 1,6,9,13,18,21 In general, this study did not uncover strong evidence that patient characteristics were related to placebo response magnitude. Meta-analyses of placebo responses in antidepressant and antipsychotic RCTs have also provided evidence that changing study characteristics drive trends in placebo response.…”
Section: Comparison With Similar Analyses In Trials In Depression Andcontrasting
confidence: 60%
See 2 more Smart Citations
“…In some of these meta-analyses, changing participant characteristics have been proposed to be responsible for the trend. 1,6,9,13,18,21 In general, this study did not uncover strong evidence that patient characteristics were related to placebo response magnitude. Meta-analyses of placebo responses in antidepressant and antipsychotic RCTs have also provided evidence that changing study characteristics drive trends in placebo response.…”
Section: Comparison With Similar Analyses In Trials In Depression Andcontrasting
confidence: 60%
“…14 This, of course, could be due either to increases in the placebo response itself and/or diminishing efficacy of new drugs. Similar analyses of randomized controlled trials (RCTs) of antipsychotic 1,17,30,32 and antidepressant 6,9,21,28,36 drugs have shown statistically significant increases in placebo response over time.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a third analysis, 3 symptom severity was not a significant predictor of the difference between active treatment and placebo, whereas enrollment at academic sites was Interrupted, aborted, or preparatory acts or behavior 1 (0.6) 0 0 Actual attempt 0 0 0 Completed suicide 0 0 0 a A subject had a positive report at baseline or during study if the subject reported any of the following suicidal ideation or behavior: (1) active suicidal ideation with some intent to act, without specific plan; (2) active suicidal ideation with specific plan and intent; (3) interrupted, aborted, or preparatory acts or behavior; (4) actual attempt; (5) completed suicide (during study). Baseline is a combination of screening visit (lifetime assessment) and baseline visit assessment.…”
Section: Discussionmentioning
confidence: 97%
“…2 In a third analysis, symptom severity was not a significant predictor of the difference between active treatment and placebo, whereas enrollment at academic sites was strongly predictive of positive treatment effects. 3 This study suggested that raters in nonacademic settings may have a tendency to overestimate baseline scores that, in turn, could lead to higher placebo responses. Consistent with this observation, results of a study by Kobak et al 4 showed that site-based raters were more likely to assign higher 17-item Hamilton Depression Rating Scale scores at baseline than centralized raters who screened patients remotely.…”
mentioning
confidence: 89%